Molecular structure formation as function of the catalytic process during the simultaneous twin polymerization of a hexadienyloxy-functionalized twin monomer with 2, 2′-spirobi[4H-1, 3, 2-benzodioxasiline]. (31st May 2019) - John, Rico; Seifert, Andreas; Schreiter, Katja; Streif, Judith; Nagel, Kevin; Spange, Stefan
Abstract: The 2-[(2 E, 4 E )-hexa-2, 4-dienyloxy]-2-methyl-4 H -1, 3, 2-benzodioxasiline twin monomer (HD-TM ) has been used in simultaneous twin polymerization (STP) with 2, 2′-spirobi[4 H -1, 3, 2-benzodioxasiline] (Spiro ) to prepare ternary hybrid materials, where in contrast thermally induced twin polymerization ofHD-TM alone failed. Depending on the used catalyst, organic-inorganic hybrid materials consisting of silica, phenolic resin and differently functionalized polysilsesquioxane are generated, as confirmed by solid-state NMR spectroscopy. During the thermally induced STP, DA reactions take place between hexadienyloxy groups and intermediately liberated ortho -quinone methide (oQM) fromSpiro . If theHD-TM concentrations are too high, the polymerization process is inhibited by trapping the oQM, which is necessary for the phenolic resin formation. Base-catalyzed STP delivers phenolic resins and hexadienyloxy-functionalized polysilsesquioxanes structures (HDPS) which can be post-derivatized with tetracyanoethylene to a DA-adduct. Acid-catalyzed STP partly leads to a cleavage of the hexadienyl group from the silicon monomer, generating highly condensed inorganic networks. Thus, the hexadienyloxy group serves both as reactant and as an internal molecular probe, allowing statements about mechanistic processes and reactive species during the STP. Graphical abstract: Image 1 Highlights: Synthesis of the twin monomer 2-[(2 E, 4 E )-hexa-2, 4-dienyloxy]-2-methyl-4 H -1, 3, 2-benzodioxasiline. Simultaneous twin polymerization with 2, 2′-spirobi[4 H -1, 3, 2-benzodioxasiline]. Formation of various molecular structures in dependence on the used catalyst. Diels-Alder reactions were evidence during the simultaneous twin polymerization. Post-derivatization can be performed for both the twin monomer and the hybrid material.